Analysis of security extension protocol in e-mail system - Jingjing SHANG; Yujia ZHU; Qingyun LIU (网络与信息安全学报)
E-mail is the main entry point for hackers to launch network attacks.Impersonating a trusted entity is an important means of e-mail forged.An attribute graph based on the e-mail authentication mechanism was built to measure the global adoption rate of e-mail security extension protocols for government agencies.Research on the deployment effect of security extension protocol was from three dimensions:e-mail content phishing,domain phishing,and letterhead phishing.The results show that about 70% of the SPF protocols are deployed in the mail systems of government agencies in various countries,and less than 30% of the DMARC protocol is deployed.The adoption rate of email identity detection is low.When forged e-mail gets in,the e-mail providers' warning mechanism for counterfeit emails need to be improved.